Capture Rate of Selected Heavy Metals In Q. Ilex L. Leaves Collected At Two Sites With Different Land Uses - Esposito, F.; Memoli, V.; Panico, S. C.; Marco, A. De; Maisto, G. (Journal of Environmental Accounting and Management, 2026)
Anthropization causes an increase of pollutants in the atmosphere that, in turn, leads to a decline of air quality. Leaves from selected tree species are useful tools to evaluate air quality as they intercept air deposition and accumulate, through stomata, pollutants in gaseous form or in fine particulate. However, leaf morphology and biochemical characteristics may be negatively affected by air pollution. The aims of the study were: i) to evaluate the concentrations of Cd, Cr, Cu, Ni and Pb in leaves and deposit on them in specimens of Q. ilex L., widely used as biomonitor; ii) to estimate the relationships between metal accumulation and morphological leaf traits (length, width, petiole length, leaf area) in two municipalities: Pomigliano (ME) and Naples (UE), respectively, characterized by mixed (urban and industrial) and urban environments. At both site typologies, the investigated metals, with the exception of Cd, were accumulated in leaf deposits, as their concentrations were higher in unwashed than washed. The comparison of the metal concentrations in deposits on leaves collected at the two site typologies highlighted that for Pb values were statistically different with concentrations higher at ME. Instead, the leaves widely differed for metal composition, with statistically higher values of Cd at UE. All the metal concentrations exceeded the chemical fingerprint, in particular Pb and Cd respectively in mixed and urban environments. Besides, the metal capture rate, an estimation of the adsorbed or captured heavy metals on the leaf surface respect to the total concentration, showed statistically lower values for Cu and Ni in leaves collected at ME, suggesting the consistent presence of fine particulate. Finally, metal accumulation in leaves collected at ME was linked to leaf morphology as leaf traits showed values lower than in leaves collected at UE.